Avaliação dimensional da via aérea superior e dos seios da face em mulheres com apneia obstrutiva do sono - Silva, Cassiana Augusta da (2018)
Obstructive sleep apnea (OSA) presents with repetitive upper airway obstruction during sleep, daytime sleepiness, decreased quality of life and severe systemic consequences. Even though OSA has a significant prevalence in the general population, many cases remain undiagnosed - mainly in woman - because some disease’s mechanisms are still unknown. The objectives were to evaluate the upper airway and facial sinus dimensions of women with and without OSA to detect possible dimensional changes that could indicate the presence of OSA and to evaluate the influence of age on the dimensions studied. Volumetric and linear measurements were taken in twenty-nine cone beam Computer tomography, in which 16 women had mild and moderate OSA and 13 women had no risk for developing the disease. Volumes evaluated were pharynx (Vfar), nasal complex (Vnas), maxillary sinuses (Vsm), frontal sinus (Vsf) and the sum of all these volumes (Vtotal). Linear measurements were nasal cavity’s width, inferior turbinate’s and soft palate’s length and width. Both groups were evaluated by age of 30-49 and 50-65 years old. No significant differences were found in volumes between groups. However, women with OSA showed a reduction on all the volumes of pneumatic cavities and increased soft palate measurements. The older group with OSA showed a significant increase in the inferior turbinate’s width. Women, in general, showed decreased volumes of facial cavities and increased measurements for lower nasal turbinate and soft palate, although not necessarily caused by the OSA.